2009
DOI: 10.1097/dmp.0b013e3181b9db91
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hurricane Katrina on the Incidence of Acute Coronary Syndrome at a Primary Angioplasty Center in New Orleans

Abstract: We found a 3-fold increased incidence of AMI more than 2 years after Hurricane Katrina. Even allowing for the loss of some local hospitals after the disaster, this represents a significant change in overall health of the study population and supports the need for further study into the health effects of chronic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 18 publications
(28 reference statements)
1
80
0
2
Order By: Relevance
“…110 Evaluations for diabetic foot increased significantly at an ECF within four weeks after a cyclone. 77 A study of diabetic patients between six and 16 months after a hurricane found worsened levels of glycated hemoglobin (7.7% to 8.1%; P < .01) compared to measurements taken in the six months before the storm, with a significant linear trend over time.…”
Section: Treatment Facility Presentations (%)mentioning
confidence: 97%
“…110 Evaluations for diabetic foot increased significantly at an ECF within four weeks after a cyclone. 77 A study of diabetic patients between six and 16 months after a hurricane found worsened levels of glycated hemoglobin (7.7% to 8.1%; P < .01) compared to measurements taken in the six months before the storm, with a significant linear trend over time.…”
Section: Treatment Facility Presentations (%)mentioning
confidence: 97%
“…In comparison, the increase in chronic illness and mortality following Hurricane Katrina has persisted for several years, although not immediately following the storm (Gautam et al 2009). The disparate periods of elevated mortality reflects the much greater level and extent of storm damage during Hurricane Katrina, which displaced a large part of the population for an extended period with disruption of normal care.…”
Section: Discussionmentioning
confidence: 95%
“…Recent evidence from Joseph et al (2009) suggests that a large number of those recently diagnosed with cancer in parts of Louisiana, Alabama and Mississippi were from the population displaced by Hurricane Katrina. As shown by Gautam et al (2009), the increase in chronic illness and mortality can persist for several years in response to continued unemployment, lack of medical insurance and living in temporary housing, in addition to noncompliance with medication, smoking and substance abuse. While further removed from the storm's physical forces, Kelman (2004) argues that indirect disaster deaths are no less a product of the event than those occurring by direct means.…”
Section: Introductionmentioning
confidence: 97%
“…Gautam et al, 73 from Tulane Medical Center in New Orleans, LA, reported a dramatic 3-fold increase in patients who presented with AMI during the 2 years following February 2006 (when Tulane reinstituted complete on-site cardiac catheterization services post-Hurricane Katrina); the increased incidence of acute CV events persisted for the 2-year period. These data suggest that a natural disaster such as a hurricane may heighten emotional stress and the incidence of AMI over time.…”
Section: Impact Of Hurricane Katrina On Acute CV Eventsmentioning
confidence: 91%
“…Emotional and stressrelated psychological exposures that are associated with an acute, transient increase in the risk for CV events include earthquakes, 68 sleep deprivation, 69 sporting events, 70 outbursts of anger, and discrete episodes of anxiety. 71,72 More recently, natural disasters, such as Hurricane Katrina, 73,74 and stock market crashes 75 have been linked to a heightened risk of acute CV events.…”
Section: Psychological Stressmentioning
confidence: 99%